Perancangan Website Profil Dan Layanan Informasi Inspektorat Provinsi Sumatera Utara - Ali Ikhwan; Nabila Rahmadani Batubara (Jurnal Publikasi Teknik Informatika, 2026)
The Inspectorate of North Sumatra Province plays a strategic role in ensuring internal government supervision, strengthening accountability, and supporting the implementation of good governance. However, limitations in integrated digital platforms have caused public information delivery to be less effective and difficult for users to access. This study aims to design and develop a Profile and Information Service Website for the Inspectorate of North Sumatra Province as a digital solution that provides institutional profiles, organizational structure, employee data, news updates, and public information request services in a structured and user-friendly manner. The system was developed using the Waterfall method, which includes requirement analysis, system design, implementation, and testing phases. The implemented system successfully delivers an informative interface that aligns with user needs and supports easy access to all main features. Blackbox testing results confirm that the system behaves as expected, with all functionalities—such as accessing profiles, viewing information centers, and submitting information requests—operating without errors. This website is expected to enhance transparency, improve public information services, and strengthen the Inspectorate’s communication with stakeholders. Future development may include integrating public complaint services, enhancing data security, and improving mobile responsiveness to support a broader and more efficient user experience.